Assessment of ferrous chloride and Portland cement for the remediation of chromite ore processing residue. (October 2015) - Jagupilla, Santhi C.; Wazne, Mahmoud; Moon, Deok Hyun
Highlights: Ferrous chloride treatment reduced Cr(VI) concentration in COPR below 20 mg kg − 1. The chemical treatment destabilized swell causing minerals in COPR. The addition of cement did not result in the formation of swell causing minerals. Use of Portland cement increased geotechnical stability of treated COPR. Abstract: Chromite Ore Processing Residue (COPR) is an industrial waste containing up to 7% chromium (Cr) including up to 5% hexavalent chromium [Cr(VI)]. The remediation of COPR has been challenging due to the slow release of Cr(VI) from a clinker like material and thereby the incomplete detoxification of Cr(VI) by chemical reagents. The use of sulfur based reagents such as ferrous sulfate and calcium polysulfide to detoxify Cr(VI) has exasperated the swell potential of COPR upon treatment. This study investigated the use of ferrous chloride alone and in combination with Portland cement to address the detoxification of Cr(VI) in COPR and the potential swell of COPR. Chromium regulatory tests, X-ray powder diffraction (XRPD) analyses and X-ray absorption near edge structure (XANES) analyses were used to assess the treatment results. The treatment results indicated that Cr(VI) concentrations for the acid pretreated micronized COPR as measured by XANES analyses were below the New Jersey Department of Environmental Protection (NJDEP) standard of 20 mg kg −1 . The Toxicity characteristic leaching procedure (TCLP) Cr concentrations for all acid pretreated samples also were reduced below the TCLP regulatory limit of 5 mg L −1 . Moreover, the TCLP Cr concentration for the acid pretreated COPR with particle size ⩽0.010 mm were less than the universal treatment standard (UTS) of 0.6 mg L −1 . The treatment appears to have destabilized all COPR potential swell causing minerals. The unconfined compressive strength (UCS) for the treated samples increased significantly upon treatment with Portland cement.